Modelos logísticos basados en variables meteorológicos para predecir niveles epidémicos de Pyricularia oryzae - Martinez, Malvina Irene; Moschini, Ricardo Carlos; Gutierrez, S.; Pedraza, Valeria Beatriz; Gattinoni, Natalia Noemí (Asociación Argentina de Fitopatólogos (AAF), 2024)
Poster